Pengaruh Strategi Pemasaran Media Sosial Terhadap Citra Merek Produk Kuliner di Kabupaten Bireuen - Alia Balqis; Zahraini Zahraini; Yusrawati Yusrawati; Al Mahfud Saputra (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of social media marketing strategy on brand image at Kue Bingkang Kak Jumi in Kuala District, Bireuen Regency. Data were collected through questionnaires using a Likert scale, while data analysis was conducted using SPSS through validity, reliability, normality, simple linear regression, t-test, and coefficient of determination analyses. The results showed that all research indicators were valid and reliable. The normality test indicated that the data were normally distributed with a significance value of 0.094 (>0.05). The regression analysis revealed that social media marketing strategy had a positive and significant effect on brand image with a significance value of 0.000 (<0.05). The coefficient of determination value of 0.531 indicated that social media marketing strategy explained 53.1% of the variation in brand image, while the remaining 46.9% was influenced by other factors outside the study. This study confirms that social media marketing is an important strategy in improving the brand image of traditional culinary MSMEs in the digital era.